Un nouveau vaccin conjugué contre le méningocoque: Que devraient faire et savoir les médecins? - Bortolussi, R (Pulsus Group Inc, 2009)
A quadrivalent meningococcal conjugate vaccine for serogroups A, C, Y and W135 (MCV4 [Menactra, sanofi pasteur, Canada]) was introduced in Canada in 2007 for persons two years of age or older. MCV4 adds three serogroups to the meningococcal serogroup C conjugate vaccine, which has been used for several years. The rates of invasive meningococcal serogroup C infection have decreased over the past decade, attributable to the meningococcal C conjugate vaccine. However, the incidence of infection caused by serogroups A, B, Y and W135 have not changed substantially. MCV4 induces the production of protective antibodies to serogroups A, C, Y and W135 in adults and children older than two years of age. Serious adverse events from MCV4 are low. In view of the effectiveness of the meningococcal C conjugate vaccine for young infants and the historic high number of meningococcal serogroup C infections in Canada, physicians should encourage and promote publicly funded immunization programs for infants starting at two months of age. MCV4 should also be given to children aged two years who are at increased risk for meningococcal infection. MCV4 may also be considered for HIV-positive children two years of age or older. All adolescents should be offered a booster dose with MCV4 or a meningococcal C conjugate vaccine at approximately 12 years of age. Both vaccines are generally safe and well tolerated.